Mengembangkan Kemampuan Sosial Melalui Metode Bermain Peran Pada Anak Usia Dini di Masa Covid-19 - Safita, Maiyida; Eliza, Delfi (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
Education during the COVID-19 pandemic has created many things that need to be considered by providing education from parents and families, so that every child's development can develop optimally. One of the developments of children that must be developed during this pandemic is social development. This study aims to find out ways that can be done to develop social development. This research was conducted using a literature study research method, in this case the researcher used several relevant research sources in the form of previous books, articles and journals, which became the focus of this research, namely developing social skills in early childhood through role playing methods, when Children's social skills can develop optimally so that later children can solve problems and make decisions without having to depend on others in the future. From the results of the study, it can be seen that one of the most appropriate ways to develop social skills in early childhood is to use the role playing method. This can be proven from several previous research results that are relevant to developing social skills through role playing methods in early childhood.